TINJAUAN TENTANG PEMENUHAN SERTIFIKASI HALAL PADA PRODUK MAKANAN RESTORAN KOREA BERDASARKAN UNDANGUNDANG NOMOR 33 TAHUN 2014 TENTANG JAMINAN PRODUK HALAL DI KOTA PEKANBARU - nudirwan, wawan; Jayakusuma, Zulfikar; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The existence of Korean restaurants has now become a culinary choice trend for Indonesian people, especially in Pekanbaru City. The problem is that consumers tend not to know whether the composition of Korean cuisine has been adapted to the identity of consumers who are predominantly Muslim. So with that, it is the responsibility of Korean restaurant businesses to ensure that the processed food is halal, both in terms of composition and processing process, as has been regulated in Undang-Undang Nomor 33 Tahun 2014 tentang Jaminan Produk Halal. The purpose of writing this thesis: first, to determine the implementation of the implementation of halal product assurance in Korean restaurants in Pekanbaru City. Second, to find out the responsibilities of business actors in providing guarantees for halal products at Korean restaurants in Pekanbaru City.The type of research used in this legal research is sociological legal research. Analysis of the data used is the author analyzes the data qualitatively. In drawing conclusions, the writer uses deductive thinking method, which is a way of thinking that draws conclusions from a general statement or proposition into a specific statement.The results of the study concluded that the implementation of the implementation of halal product assurance at Korean restaurants in Pekanbaru City had not run optimally. There are still business actors who do not apply JPH to their restaurant business. Of the 10 Korean restaurants, 5 restaurants do not include halal labels, 2 restaurants fake halal labels, 2 other restaurants include halal labels but are not easily seen by consumers, 1 restaurant has halal labels that are easy to see. For halal certificate ownership, 8 restaurants are halal certified by MUI, 2 other restaurants are not halal certified